SnO2@N‐Doped Carbon Hollow Nanoclusters for Advanced Lithium‐Ion Battery Anodes. Issue 6 (February 2016) - Li, Lu; Zhang, Lingyu; Chai, Fang; Wang, Tingting; Li, Zilu; Xie, Haiming; Wang, Chungang; Su, Zhongmin
Abstract: Invited for the cover of this issue are Chungang Wang and Zhongmin Su from the Northeast Normal University, Changchun, and Fang Chai from the Harbin Normal University, Harbin, P. R. China. The cover image shows monodisperse SnO2 @N‐doped carbon hollow nanoclusters that enhance the performance of lithium‐ion batteries. Abstract : The SnO2 @N‐C hollow nanoclusters that we developed exhibit excellent electrochemical performance... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 812 ff .